Penggunaan Software Lontar Dalam Penelusuran Informasi Oleh Pemustaka Di UPT Perpustakaan Universitas Riau - Yuli Astuti (Perpustakaan Universitas Riau, 2013)
The purpose of this study is to investigate the use of Papyrus in information retrieval software by students in the library of the University of Riau. The research was conducted in the University library Riau samples in this study as many as 50 students who visited the Riau University Library Unit. With accidental sampling technique. This research is descriptive method. The formula used is simple linear regression formula: Y = a + e + BX1. The calculation formula is processed using SPSS software ver. 17 for windows. Regarding satisfaction in using the palm software, is dominated by the answers of respondents undecided respondents were 22 to 44%, to answer answered agree and disagree with each of the 11 respondents with a percentage of 22%, whereas the response was strongly agree with 6 respondents, amounting to of 12%. The results of this study are expected to be useful for the improvement and enhancement software Lontar in information retrieval by pemustaka.